Assessment of the effects of controlled frequency breathing on lactate levels in swimming - Key, M. A.; Eschbach, C. L.; Bunn, J. A. (Journal of Athletic Enhancement, 2014)
Objective: The purpose of this study was to assess differences in performance and physiological variables after a 100-yard freestyle swim in free-breathing and controlled-frequency breathing conditions. Methods: A randomly assigned maximal effort 100-yd swim test was conducted twice, once with normal breathing (NB) pattern (1 breath every 2-3 strokes), and the second using controlledfrequency breathing (CFB) pattern (1 breath every 7 strokes) in 21 trained female swimmers (19.0 ± 1.1 years). Post-swim blood lactate levels, heart rate, and time to completion were measured and assessed after completion of each bout. Blood samples were taken from the earlobe at rest (prior to the bout), 0-min, 1.5-min, 3-min, and 5-min post-swim. Heart rate was taken at rest and at the same time points as blood lactate. RESULTS: There was no difference in blood lactate at 0-min (NB 4.34 ± 0.62 mmol/L; CFB 4.56 ± 0.34 mmol/L), 1.5-min (NB 7.24 ± 0.56 mmol/L; CFB 5.90 ± 0.62 mmol/L), 3-min (NB 6.84 ± 0.63 mmol/L; CFB 6.04 ± 0.52 mmol/L), and 5-min (NB 6.10 ± 0.61 mmol/L; CFB 4.7 ± 0.51 mmol/L) post-swim. Post-exercise heart rate was significantly higher (p = 0.02) in NB trial (184.9 ± 12.0 bpm) than the CFB trial (174.8 ± 14.8 bpm). The NB 100-yard swim averaged 60.23 ± 0.53 s, and the CFB trial average 61.36 ±.62 s (p>0.05). Conclusions: The results suggest that CFB has no significant immediate effect on blood lactate levels after high intensity swimming races. The significant difference in heart rate between the CFB and NB swims could be explained by the decrease in ventilation produced by the CFB swim causing the heart rate to slow even during exercise.